2019
DOI: 10.1186/s12882-019-1228-y
|View full text |Cite
|
Sign up to set email alerts
|

The value of maintaining normokalaemia and enabling RAASi therapy in chronic kidney disease

Abstract: BackgroundPeople with chronic kidney disease (CKD) are at an increased risk of developing hyperkalaemia due to their declining kidney function. In addition, these patients are often required to reduce or discontinue guideline-recommended renin-angiotensin-aldosterone system inhibitor (RAASi) therapy due to increased risk of hyperkalaemia. This original research developed a model to quantify the health and economic benefits of maintaining normokalaemia and enabling optimal RAASi therapy in patients with CKD.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 57 publications
(52 reference statements)
2
19
0
1
Order By: Relevance
“…The findings from this study corroborate results from a recent study conducted by Evans and colleagues, which demonstrated the value of maintaining normokalaemia in CKD in terms of improved survival, delayed dialysis onset and lower cost from the perspective of the health‐care system in the United Kingdom (UK) . The agreement between the results of the current analysis based on real‐world Italian data and the study conducted in UK, seems to indicate likely generalisability of the reported predictions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings from this study corroborate results from a recent study conducted by Evans and colleagues, which demonstrated the value of maintaining normokalaemia in CKD in terms of improved survival, delayed dialysis onset and lower cost from the perspective of the health‐care system in the United Kingdom (UK) . The agreement between the results of the current analysis based on real‐world Italian data and the study conducted in UK, seems to indicate likely generalisability of the reported predictions.…”
Section: Discussionsupporting
confidence: 90%
“…The international expert panel of Kidney Disease: Improving Global Outcomes (KDIGO) Guidelines has repeatedly brought to attention of nephrology community the importance of conservative care as rational treatment alternative to dialysis even in advanced CKD because dialysis initiation associates with a still dramatically increase in mortality, poorer quality of life in survivors, and striking hike of economic costs [30][31][32][33][34]. The findings from this study corroborate results from a recent study conducted by Evans and colleagues, which demonstrated the value of maintaining normokalaemia in CKD in terms of improved survival, delayed dialysis onset and lower cost from the perspective of the health-care system in the United Kingdom (UK) 35. The agreement between the results of the current analysis based on real-world Italian data and the study conducted in UK, seems to indicate likely generalisability of the reported predictions.…”
supporting
confidence: 81%
“…A recent study assessed the cost-effectiveness of sustained serum potassium level control and ongoing RAAS inhibitor therapy using a patient-level simulation model in patients with CKD. 26 In this study, sustained serum potassium level control and ongoing RAAS inhibitor therapy resulted in longer life expectancy (by 2.36 years), delayed onset of end-stage renal disease (by 5.4 years), quality-adjusted life-year gains (1.04 year), and cost savings of £3,135 ($3,871) compared with the absence of RAAS inhibitor use to prevent hyperkalemia. Evidence of the cost-effectiveness of long-term serum potassium level management has become increasingly important, particularly with the recent introduction of newer potassium-binding agents such as patiromer and sodium zirconium cyclosilicate in clinical practice with improved tolerability for continuous use.…”
Section: Discussionmentioning
confidence: 70%
“…The early hyperkalemia resolution is attributed to fast-acting helpful mediations administered using intravenous solutions and the control of NSAIDs. The prevalence of NSAIDs as a cause of hyperkalemia reflects the population, which has a high incidence of kidney diseases and coronary artery diseases, which are less likely to be treated NSAIDs [ 16 ]. The method of collecting data to measure exposure to drugs through the records of the drugs administered before a hyperkalemia episode is controversial [ 17 ].…”
Section: Discussionmentioning
confidence: 99%